(untitled) (Research, Society and Development, 2022)
The first human retrovirus isolated was the Human Cell Lymphotropic Virus (HTLV), belonging to the Retroviridae family, which infects TCD4+/TCD8+ cells. In a blood bank, seroconversion of donors by this virus is investigated by blood surveillance and some studies have shown that, despite the reduction of transfusion-transmitted diseases, the rate of seroconversion has increased. Aim: To define the portfolio of articles on HTLV seroconversion in blood banks. Methodology: This documentary-based study is based on bibliometric methodology, which uses quantitative scientific analysis methods. Data collection for this article was carried out in October and November 2021, in the Web of Science database, a platform that provides a wide range of scientific data for many academic disciplines. Results And Discussions: A low incidence of seroconversion to HTLV, either type 1 or 2, was found in blood banks. The authors described that the seroconversion rate is not high due to the methods used as barriers to transfusion safety, which are the clinical, serological, and immunological screening, methodologies used and standardized in all blood banks. Conclusion: This study allows us to help the scientific community with a documentary portfolio on the subject through mathematical and statistical aspects, the bibliometric indexes.